EFL university students’ perceptions about cross-cultural presentations via videoconferencing - Yu, Li-Tang; Wu, Hsiao-Ping (Frontiers in Psychology, 2023)
This study aims to examine EFL university students’ perceptions about cross-cultural videoconferencing presentations for professors in the United States. Nineteen Taiwanese English-as-foreign-language university students who studied in a night program for a bachelor’s degree attended the study. Each of them was free to choose a topic related to Taiwanese cultures and individually made a 25-minute presentation plus a five-minute question-and-answer session. After the presentation, they watched recordings of their presentations, completed a five-point Likert-scale attitude survey, and wrote down their reflections. The results showed that the participants were positive about the activity. Based on the analysis of their reflections, the participants acknowledged various aspects of the cross-cultural presentations, such as the opportunities to use English meaningfully, motivation to prepare for the project, and the authentic nature of the interaction. However, the participants had concerns about their language abilities, anxiety, and limited preparation time. Finally, they mentioned the impact the presentation had on them. Pedagogical implications and suggestions for future research are provided.